Antifungal lactic acid bacteria isolated from fermented beverages with activity against Colletotrichum gloeosporioides. (June 2019) - Barrios-Roblero, Carolina; Rosas-Quijano, Raymundo; Salvador-Figueroa, Miguel; Gálvez-López, Didiana; Vázquez-Ovando, Alfredo
Abstract: LAB with antifungal activity against the phytopathogen Colletotrichum gloeosporioides, which causes anthracnose in papaya were isolated and identified. Ten LAB strains with strong antifungal capacity were isolated from two samples of fermented beverages (Tepache and Tejuino) and identified as Lactobacillus plantarum (3 strains), L. paracasei (4 strains) and L. pentosus (3 strains) by sequencing the 16S rRNA gene fragment at the species level (100% homology). All the strains inhibited spore germination by at least 60% and mycelial growth by 100%. These results can potentially contribute to the search for innocuous biocontrol agents of the fungus that causes anthracnose in fruits. Highlights: Lactic acid bacteria (LAB) that showed antifungal activity were isolated. Ten LAB showed antifungal activity against Colletotrichum gloeosporioides . LAB were identified as Lactobacillus plantarum, L. paracasei and L. pentosus.